Formação inicial e prática docente nos anos iniciais do ensino fundamental: uma experiência em escolas públicas no município de Vargem Grande/MA - SOUSA, Jerusa Roiz de (2023)
This research aimed to analyze the initial training of teachers and the repercussions on the teaching practice developed in Elementary School I stage, in municipal public schools, in the municipality of Vargem Grande/MA. The investigation emerged from an interest in deepening knowledge about initial formation and the teaching practice developed by teachers at this level of education, considering personal experience in the field of institutionalized education in the aforementioned municipality. You specific objectives consisted of: knowing the historical process of formation of teachers in Brazil, having as a timeframe the 30s of the twentieth century to threshold of the 21st century; analyze the demands of the teaching practice for the teacher of the Elementary Education, in public schools in Vargem Grande/MA; identify the educational demands in this municipality, in the context of policies directed for Basic Education; discuss how initial training has been carried out in practice teacher of elementary school teachers in the municipality in question. You research participants were 7 (seven) elementary school teachers I stage, 2 (two) general managers, and 2 (two) pedagogical advisors. The rationale theoretical-methodological research was based on studies developed by Chizzotti (2003), Duarte (2010, 2021), Duarte and Gama (2017), Fonseca (2002), Freire (1996, 1997, 2001), Franco (2002), Minayo (2002, 2012), Saviani (1997, 2005, 2009, 2013), among others. This is a qualitative epistemological research. critical, in which the questionnaire and the semi-structured interview were used to collect fundamental information in line with the proposed objectives. The analysis of enunciations of these speeches as well as documents related to the object of research was carried out according to the methodological procedure of content analysis, in the light of the theoretical framework that supported this investigation. The research showed that the initial training of teachers is considered essential to the work that perform at school, but there is a strong predominance of demands directed at preparation of students to meet the demands of external assessments, for through programs structured under business molds. Such prescriptions, which limit the knowledge to be worked on, become hegemonic in the context of educational system, with serious damage to the desired quality of the public school.